2011
DOI: 10.5897/ajb10.1302
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of direct dyes by low cost rice husk: Effect of treatments and modifications

Abstract: In the present study, free, carboxymethyl cellulose (CMC)-immobilized, polyvinyl alcohol (PVA)-alginate immobilized and chemically treated rice husk biomass was used for the biosorption of Everdirect Orange-3GL and Direct Blue-67 dyes. Maximum biosorption capacity of free, immobilized and hydrochloric acid treated biomass was observed for both dyes at low pH. Comparative study of free, immobilized and HCl treated biomass showed that, the HCl treated biomass exhibited more biosorption capacity (29.98 and 37.92 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 55 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The adsorption of DB-K 2 RL was increased from 58.36% to 78.62% (Fig. 4) with an increase in initial concentration of dye up to 50 ppm, after that it decreased even by increasing the initial concentration of dye (Safa and Bhatti 2011).Initially at lower concentration of dye number of sites on sorbent were greater, therefore percentage removal of dye was increased (Aksu and Kabasakal 2004). At higher concentration, active adsorption sites were insufficient and adsorption rate decreased (Orfaco et al, 2006).…”
Section: Ii) Effect Of Adsorbent Dosagementioning
confidence: 94%
See 1 more Smart Citation
“…The adsorption of DB-K 2 RL was increased from 58.36% to 78.62% (Fig. 4) with an increase in initial concentration of dye up to 50 ppm, after that it decreased even by increasing the initial concentration of dye (Safa and Bhatti 2011).Initially at lower concentration of dye number of sites on sorbent were greater, therefore percentage removal of dye was increased (Aksu and Kabasakal 2004). At higher concentration, active adsorption sites were insufficient and adsorption rate decreased (Orfaco et al, 2006).…”
Section: Ii) Effect Of Adsorbent Dosagementioning
confidence: 94%
“…Figure 3: Effect of amount of biosorbent on the sorption of DB-K 2 RL on T. latifolia leaves ii) Effect of dye concentration:The adsorption of DB-K 2 RL was increased from 58.36% to 78.62% (Fig.4) with an increase in initial concentration of dye up to 50 ppm, after that it decreased even by increasing the initial concentration of dye(Safa and Bhatti 2011).Initially at lower concentration of dye number of sites on sorbent were greater, therefore percentage removal of dye was increased(Aksu and Kabasakal 2004). At higher concentration, active adsorption sites were insufficient and adsorption rate decreased(Orfaco et al, 2006).The results reported by(Paola et al, 2004) revealed that the adsorption of 2,4-dichlorophenoxyacetic acid was fast at the initial stages of contact time and was slowed down near equilibrium due to high affinity of the interacting groups on the surface of the activated carbon, similar results were obtained in our study.…”
mentioning
confidence: 96%
“…The optimal condition remained same i.e., pH, contact time (2 h), temperature (27 °C) and 150 rpm shaking speed. It was found that adsorption ability decreased with rise of HEC/PANI-PPy which is ascribed to aggregation of the adsorbent with concomitant rise in adsorbent concentration and decreasing availability of surface for adsorption [ 48 ].…”
Section: Dyes Adsorption and Effect Of Different Parametersmentioning
confidence: 99%
“…Moreover, a survey of literature has disclosed that CMC has been produced by extracting cellulose from ample biosources like sago waste, wheat straw, rice straw, corn husk, rice husk, cotton linters, banana leaves, bagasse, and others . But the most common waste on the domestic level that is overlooked is matchstick (MS) waste made of bamboo.…”
Section: Introductionmentioning
confidence: 99%